PEMANFAATAN LIMBAH GROUND GRANULATED BLAST FURNACE SLAG (GGBFS) DAN FLY ASH SEBAGAI PENGGANTI SEBAGIAN SEMEN PADA KUAT TEKAN BETON - Raafidiani, Reni; Putri, Asti Aprillia Rekta; Febriansya, Aditia (UPPM Politeknik TEDC Bandung, 2025)
Ground Granulated Blast Furnace Slag (GGBFS) and Fly Ash are two industrial by-products with great potential as partial cement substitutes in concrete mixtures. GGBFS is a by-product of the iron smelting process in the steel industry. Once cooled and ground into a fine powder, it exhibits pozzolanic and cementitious properties. Meanwhile, Fly Ash, the residual ash from coal combustion in power plants, also possesses pozzolanic characteristics. The use of GGBFS and Fly Ash not only reduces the reliance on Portland cement but also provides various technical benefits, such as improving the durability of concrete, reducing heat of hydration, and enhancing long-term strength. Additionally, utilizing these materials aligns with the principles of sustainable development by reducing industrial waste and lowering carbon emissions. This study employs Ground Granulated Blast Furnace Slag (GGBFS) and Fly Ash as partial substitutes for cement in the production of geopolymer concrete. The proportion of GGBFS used is 50% of the total cement weight, while Fly Ash is applied in proportions of 5%, 10%, and 15% of the total cement weight. The concrete was designed with a target compressive strength of 26 MPa. Tests were conducted on 24 cylindrical concrete samples measuring 15 x 30 cm. The results revealed that the average compressive strength of concrete at 28 days was 34.15 MPa for normal concrete. For mixtures with a PCC:GGBFS:Fly Ash ratio of 45:50:5, the average compressive strength was 23.46 MPa; for a 40:50:10 ratio, the average strength was 18.48 MPa; and for a 35:50:15 ratio, the average strength was 19.54 MPa. Based on the analysis, the mix with 50% GGBFS and 5% Fly Ash was determined to be the optimal combination, as it achieved the highest compressive strength among all variations, at 23.46 MPa. This demonstrates that this combination can be utilized as a partial cement replacement for concrete production, considering specific requirements and its potential applications.